Sexual Dysfunction at the Onset of Type 2 Diabetes: The Interplay of Depression, Hormonal and Cardiovascular Factors. (1st August 2014) - Corona, Giovanni; Giorda, Carlo B.; Cucinotta, Domenico; Guida, Piero; Nada, Elisa
Abstract: Introduction: Several data have emphasized the importance of early diagnosis of erectile dysfunction (ED) and meticulous cardiovascular investigation in the type 2 diabetic mellitus (T2DM) patients. Aim: To estimate the prevalence of ED and its associated determinants in a sample of male patients with new or recently diagnosed T2DM. Methods: The SUBITO‐DE study is an observational, multicenter, prospective study involving 27 Italian diabetes centers. Male patients recently diagnosed with T2DM were consecutively interviewed by their attending physician at the diabetes care centers and asked whether they had experienced a change in their sexual function or found it unsatisfactory. Those responding positively were then invited to participate in the study. Main Outcome Measure: Several hormonal and biochemical parameters were studied. Results: A nonselected series of 1, 503 patients was interviewed, 499 of which (mean age, 58.8 ± 8.8 years) entered the study, yielding a final enrolment rate of 33.3%. ED was classified as mild in 19.4%, mild‐to‐moderate in 15.4%, moderate in 10.4%, and severe in 21.6% of patients, respectively. In addition, premature ejaculation, delayed ejaculation, and hypoactive sexual desire (HSD) were comorbid in 28.3%, 32.9%, and 58.4%, respectively. Finally, hypogonadism, showed an estimated prevalence of almost 20%. Both organic (at least one chronic DM‐associated complication) and psychological factors (severe depressive symptoms) increased the risk of ED. Severe depressive symptoms were also associated with ejaculatory problems, HSD, and hypogonadism. Conclusions: A high prevalence of sexual dysfunction in men with recently diagnosed T2DM was detected. Early diagnosis of ED could help prevent emotional and physical discomfort in men and aid in identifying reversible cardiovascular risk factors. Screening of sexual dysfunction should become a part of routine care in the management of T2DM patients.